2013
DOI: 10.1051/0004-6361/201220298
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive survey for13CO, CN, H2CO, and SO in the disks of T Tauri and Herbig Ae stars

Abstract: Aims. We investigate the suitability of several molecular tracers, in particular CN N = 2−1 line emission, as a confusion-free probe of the kinematics of circumstellar disks. Methods. We use the IRAM 30-m telescope to perform a sensitive search for CN N = 2−1 in 42 T Tauri or Herbig Ae systems located principally in the Taurus-Auriga region. 13 CO J = 2−1 is observed simultaneously to provide an indication of the level of confusion with the surrounding molecular cloud. The bandpass also contains two transition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
153
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(180 citation statements)
references
References 75 publications
25
153
2
Order By: Relevance
“…Most disks in our sample were found to be smaller than those in the Guilloteau et al (2013) sample. However, this is probably a selection bias: the targets of our ALMA study have T eff s cooler than the stars in our pilot studies (Guilloteau et al 2013. Indeed, there is no difference in disk size in our new sample between the L1495 and L1688 regions.…”
Section: Spectral Lines From Diskscontrasting
confidence: 59%
See 1 more Smart Citation
“…Most disks in our sample were found to be smaller than those in the Guilloteau et al (2013) sample. However, this is probably a selection bias: the targets of our ALMA study have T eff s cooler than the stars in our pilot studies (Guilloteau et al 2013. Indeed, there is no difference in disk size in our new sample between the L1495 and L1688 regions.…”
Section: Spectral Lines From Diskscontrasting
confidence: 59%
“…To overcome this, we tested the detectability of the hyperfine-split CN 2-1 transition radiated by circumstellar disks. We found that the CN lines were good tracers of disk emission of targets in the Taurus SFR and were free of molecular absorption (Guilloteau et al 2013). We then used the Plateau de Bure interferometer to measure the masses of 11 stars in the Taurus SFR ).…”
Section: Spectral Lines From Disksmentioning
confidence: 99%
“…DL Tau A dust disk around DL Tau was first detected by Beckwith et al (1990), followed by the observation of CO gas (Koerner & Sargent 1995;Simon et al 2000), CN , and H 2 CO (Guilloteau et al 2013), despite strong confusion. While the CO and CN extends out to ∼460 au, the dust disk is smaller, with an outer radius of 150-180 au (Guilloteau et al 2011;Kwon et al 2015).…”
Section: Objects With Low Equivalent Widthmentioning
confidence: 99%
“…On the other hand, sulfur bearing species have long been searched in protoplanetary disks associated with evolved young stellar objects (i.e. Class I-II) but only CS has been routinely observed while SO is hard to detect: Dutrey et al (2011) reported no detection of SO (and H 2 S) from three prototypical protoplanetary disks; Fuente et al (2010) reported a detection in the disk of the T Tauri star AB Aur; and Guilloteau et al (2013) showed that SO is exceptionally observed in disks with only one definite detection on a sample of 42 T Tauri and Herbig Ae stars towards 04302+2247. The statistics regarding disks around Class 0 protostars is even poorer.…”
Section: Introductionmentioning
confidence: 99%